2022
DOI: 10.3390/cells11182854
|View full text |Cite
|
Sign up to set email alerts
|

Human Allogeneic Liver-Derived Progenitor Cells Significantly Improve NAFLD Activity Score and Fibrosis in Late-Stage NASH Animal Model

Abstract: Accumulated experimental and clinical evidence supports the development of human allogeneic liver-derived progenitor cells (HALPCs) to treat fibro-inflammatory liver diseases. The aim of the present study was to evaluate their therapeutic effect in a non-alcoholic steatohepatitis (NASH)-STAM mouse model. The immune signaling characteristics of HALPCs were first assessed in vitro. Upon inflammation treatment, HALPCs secreted large amounts of potent bioactive prostaglandin E2 and indoleamine 2,3-dioxygenase, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…A preliminary efficacy study demonstrated normalization of ALT and AST serum levels and gradual decreasing of bilirubin and triglyceride levels as well as IL-6 levels and fibrosis over a period of 6 months [177]. In the early-and late-stage NASH mouse models, these human allogeneic liver-derived progenitor cells exhibited pronounced anti-inflammatory and anti-fibrotic effects [178]. In another clinical trial (UMIN000022601), MSCs showed a significant therapeutic effect in patients with NAFLD/NASH.…”
Section: Cell Therapy Of Nash Based On the Cross-talk Between Transpl...mentioning
confidence: 99%
“…A preliminary efficacy study demonstrated normalization of ALT and AST serum levels and gradual decreasing of bilirubin and triglyceride levels as well as IL-6 levels and fibrosis over a period of 6 months [177]. In the early-and late-stage NASH mouse models, these human allogeneic liver-derived progenitor cells exhibited pronounced anti-inflammatory and anti-fibrotic effects [178]. In another clinical trial (UMIN000022601), MSCs showed a significant therapeutic effect in patients with NAFLD/NASH.…”
Section: Cell Therapy Of Nash Based On the Cross-talk Between Transpl...mentioning
confidence: 99%